(untitled) - Osswald, Tim A. (Munich, 2003)
Engineering Design Properties - covering the different properties that need to be considered when designing a polymer component - from mechanical properties to failure mechanisms, electrical properties, acoustic properties, and permeability of polymers. The first edition was praised for the vast number of graphs and data that can be used as a reference. A new table in the appendix containing material property graphs for several polymers further strengthens this attribute. A new chapter introducing polymers from a historical perspective not only makes the topic less dry, but it also provides a chance to shade light on the role polymers played, for better and for worse, while shaping today's industrial world. The most important change made to this edition is the introduction of real-world examples and a variety of problems at the end of each chapter.
Keywords: Polymers,Plastics,Hợp chất cao phân tử,Chất dẻo